Urban Open Space: Designing For User Needs (Case Studies Land Community Design) - Francis Mark (ADBS, 2003)
Research has shown that successful public spaces are ones that are responsive to the needs of their users, are democratic in their accessibility, and are meaningful for the larger community and society. While considerable research has been done on needs and conflicts in open space, no one document integrates all this knowledge and makes it available to professionals, students, and researchers.